Physicochemical and functional properties of Lycium ruthenicum pectin by different extraction methods - Wu, Ziyang; Qin, Dan; Li, Hehe; Guo, Dongqi; Cheng, Huan; Sun, Jinyuan; Huang, Mingquan; Ye, Xingqian; Sun, Baoguo (Frontiers in Nutrition, 2022)
Three different extraction methods were used to extract high-temperature water-extracted pectin (HWp), high-temperature acid-extracted pectin (HAp), and high-temperature alkali-extracted pectin (HALp) from Lycium ruthenicum. The physicochemical properties, structure, and functional properties of three different pectins were studied. The results showed that HWp and HALp can extract rhamnogalacturonan-I (RG-I) from L. ruthenicum better. Through structural feature analysis, HWp and HALp have a branched structure, and HWp has a higher degree of esterification than HAp and HALp. Zeta potential results show that HWp solution is more stable. The thermal analysis results show that the thermal stability is HALp > HAp > HWp. HWp has the highest viscosity. The inhibitory activity results showed that HWp, HAp, and HALp have a certain inhibitory effect on α-glucosidase activity. This study shows the effects of different extraction methods on the properties of L. ruthenicum pectin and aims to provide a theoretical basis for the pharmaceutical and food industries to choose more suitable pectin extraction methods.